Arithmetic Counting Techniques through Manipulatives: Effect on the Numeracy Skills of Grade 1 Pupils - Vendicacion, Edlyn G.; Huevos, Cecilia G.; Espiritu Jr., Melchor L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study aimed to determine the effectiveness of Arithmetic Counting Techniques through manipulatives on the numeracy skills of Grade 1 pupils in adding and subtracting numbers. The study employed a quasi-experimental design, specifically one- group pretest and posttest involving 30 Grade one pupils of Lias Elementary School for the School Year 2023- 2024 who did not meet the prescribed 60% minimum proficiency level (MPL) during the conduct of the Regional Diagnostic Assessment (RDA) as per Regional Memorandum No. 502, s. 2022. The pupil-respondents were exposed to a variety of manipulatives such as shoot the goal, whack-a-mole, spin the numeracy wheel, light up the Math path, lead the trail, and push the abacus that offered a hands-on approach to learning. Results showed that the use of Arithmetic Counting Techniques through manipulatives has a significant effect on pupils’ numeracy skills, specifically in adding and subtracting numbers, as manifested in the associated p-value of .000, which is less than the .05 level of significance and in the increase of pretest and posttest mean scores of 7.77 and 18.80, respectively. Furthermore, the computed effect size (r) is -0.875 based on the z value, which implies that the material has a large effect on the numeracy skills of Grade 1 learners. Utilizing Arithmetic Counting Techniques through manipulatives is highly recommended to provide pupils with concrete, meaningful, and hands-on learning opportunities that can positively strengthen their numeracy skills and present lessons in a more engaging, innovative, and dynamic means.